Age and growth in Peale's dolphin (Lagenorhynchus australis) in subantarctic waters off southern South America - Boy, Claudia Clementina (2011)
The Peale´s dolphin, Lagenorhynchus australis, is a mainly coastal and one of the most often seen species off southernmost South America from 33°S off Chile and 38°S off Argentina to south of Cape Horn. Although a common species, its IUCN status is “Data Defficient”, so any information on this species is relevant. Age, growth and physical maturity were examined in skeletons of 57 specimens of this species, mostly from the coasts of Tierra del Fuego, Argentina; this represents most of the known specimens of this species available in museum and private collections. Most specimens were by-catch in shore-set gillnets or had been harpooned for crab bait. Age was determined for 23 specimens, all from Tierra del Fuego. The maximum age was 13 years for a 199 cm female. The largest female in this survey was 210 cm, the largest male 205 cm in total length (12 years), but this probably does not represent the maximum length for this species. Only two animals, of 12 and 13 years, were physically mature. Animals reach asymptotic length (188 cm) with less than the 30% of the vertebral epiphyses fused. The animals in this study were mainly subadults, as has been found for other southern by-caught dolphins. Growth was studied for total length using 18 osteological characters with the Gompertz model. We propose that zygomatic width can be used to estimate total length for incomplete beach-cast specimens.